2018
DOI: 10.3389/fimmu.2018.02895
|View full text |Cite
|
Sign up to set email alerts
|

Role of Herpes Simplex Virus Type 1 (HSV-1) Glycoprotein K (gK) Pathogenic CD8+ T Cells in Exacerbation of Eye Disease

Abstract: HSV-1-induced corneal scarring (CS), also broadly referred to as Herpes Stromal Keratitis (HSK), is the leading cause of infectious blindness in developed countries. It is well-established that HSK is in fact an immunopathological disease. The contribution of the potentially harmful T cell effectors that lead to CS remains an area of intense study. Although the HSV-1 gene(s) involved in eye disease is not yet known, we have demonstrated that gK, which is one of the 12 known HSV-1 glycoproteins, has a crucial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 106 publications
1
26
0
Order By: Relevance
“…The correlation between increased eye disease and an increase in CD8 ϩ T cells agrees with our previous findings (36-39, 45, 46). For example, overexpression of gK, a viral glycoprotein that functions in viral egress (reviewed in Jaggi et al [47]), produced increased eye disease that was ameliorated by depleting CD8 ϩ T cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between increased eye disease and an increase in CD8 ϩ T cells agrees with our previous findings (36-39, 45, 46). For example, overexpression of gK, a viral glycoprotein that functions in viral egress (reviewed in Jaggi et al [47]), produced increased eye disease that was ameliorated by depleting CD8 ϩ T cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…keratitis, conjunctivitis, and anterior uveitis (6)(7)(8). Indeed, HSV-1-induced keratitis represents one of the leading causes of infectious blindness in the United States (6,9,10).…”
mentioning
confidence: 99%
“…Other HSV-1 genes have also failed to replace LAT. Previously, we found that the replacement of LAT with HSV-1 glycoprotein K (gK) also produced significant eye disease in C57BL/6 mice (9,65,68,69). CD80 is unique among tested host genes expressed by recombinant HSV-1, as we have shown that replacing LAT with the host cytokine IFN-␥ or IL-4 did not restore latency, reactivation, or immune exhaustion (70).…”
Section: Discussionmentioning
confidence: 99%